2021
DOI: 10.3389/fpsyt.2021.682454
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-Specific Statistical Modeling Identifies Interplay Between Gastrointestinal Microbiome and Neurobehavioral Outcomes in Patients With Autism: A Case Control Study

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with unclear mechanisms of pathogenesis. Gastrointestinal microbiome alterations were found to correlate with ASD core symptoms, but its specific role in ASD pathogenesis has not been determined. In this study, we used a case-control strategy that simultaneously compared the ASD gastrointestinal microbiome with that from age-sex matched controls and first-degree relative controls, using a statistical framework accounting for confounders such as ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In the current study, specific bacterial genera altered significantly after HKC administration, and showed a significant correlation with changes in metabolite levels and disease indicators, suggesting that they may be associated with the mechanism of effects of HKC in treatment of DN. Among the differential intestinal bacteria, Phyllobacterium has been reported to be associated with the diseases in humans, such as liver cirrhosis and non‐liver cirrhosis‐induced HCC, and significantly enriched in the autism spectrum disorders patients and the cholestatic infants (Guo et al, 2018 ; Huang et al, 2021 ; Zheng, Wang, et al, 2020 ). Similarly, a recent study has demonstrated that Weissella confusa was higher in KK‐Ay mice with T2D (Liu et al, 2021 ) while other studies have shown that Weissella decreased after treatment with some effective medications in an animal model of T2D (Hu et al, 2019 ; Zheng, Chen, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, specific bacterial genera altered significantly after HKC administration, and showed a significant correlation with changes in metabolite levels and disease indicators, suggesting that they may be associated with the mechanism of effects of HKC in treatment of DN. Among the differential intestinal bacteria, Phyllobacterium has been reported to be associated with the diseases in humans, such as liver cirrhosis and non‐liver cirrhosis‐induced HCC, and significantly enriched in the autism spectrum disorders patients and the cholestatic infants (Guo et al, 2018 ; Huang et al, 2021 ; Zheng, Wang, et al, 2020 ). Similarly, a recent study has demonstrated that Weissella confusa was higher in KK‐Ay mice with T2D (Liu et al, 2021 ) while other studies have shown that Weissella decreased after treatment with some effective medications in an animal model of T2D (Hu et al, 2019 ; Zheng, Chen, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 met the inclusion criteria described above and were included in this analysis. We identified one dataset deposited in the Sequence Read Archive (SRA) with its respective metadata, that was not yet published but published during manuscript preparation 39 . Lastly, we utilized open-source data generated from the American Gut Project (AGP) to cultivate an additional dataset of ASD children and controls.…”
Section: Methodsmentioning
confidence: 99%
“…Most children show some abnormal behavior symptoms only at about 18–24 months, while other specific functional characteristics may only be found at an older age ( Borghi and Vignoli, 2019 ). Current studies indicate that there are multiple subtypes of ASD, potentially caused by different routes of pathophysiology and each with diverse comorbid psychiatric and medical conditions (e.g., gastrointestinal symptoms, allergies, sleep disorders) ( Huang et al, 2021 ). However, this heterogeneity is not addressed by the conventional DSM5-based behavioral diagnostic criteria.…”
Section: Gut Dysbiosis In Autism Spectrum Disordermentioning
confidence: 99%